2017
DOI: 10.1007/s11102-017-0791-0
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor ligands in the treatment of acromegaly

Abstract: First-generation somatostatin receptors ligands (SRL) are the mainstay in the medical treatment of acromegaly, however the percentage of patients controlled with these drugs significantly varies in the different studies. Many factors are involved in the resistance to SRL. In this review, we update the physiology of somatostatin and its receptors (sst), the use of SRL in the treatment of acromegaly and the factors involved in the response to these drugs. The SRL act through interaction with the sst, which up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 73 publications
2
69
0
10
Order By: Relevance
“…The SRLs octreotide, lanreotide and pasireotide, as well as the dopamine agonist cabergoline, bind cognate receptors in the adenoma and suppress GH secretion; the GH antagonist pegvisomant blocks GH action in the periphery and blocks generation of IGF1 (refs [57][58][59] ).…”
Section: Biochemical Results Of Medical Therapymentioning
confidence: 99%
“…The SRLs octreotide, lanreotide and pasireotide, as well as the dopamine agonist cabergoline, bind cognate receptors in the adenoma and suppress GH secretion; the GH antagonist pegvisomant blocks GH action in the periphery and blocks generation of IGF1 (refs [57][58][59] ).…”
Section: Biochemical Results Of Medical Therapymentioning
confidence: 99%
“…2 However, the response to SSAs treatment is largely variable. [3][4][5] Recent prospective studies have shown success rates for SSAs (20%-40% of patients) lower than initially reported (recently reviewed in 6 ). While differences in patient selection and definitions of response to treatment may partly account for these discrepancies among published studies, there is certainly considerable variability in the efficacy of SSAs among patients in each individual study.…”
Section: Consensus Guidelines Recommend Somatostatin Analogues (Ssas)mentioning
confidence: 97%
“…The control rates with pegvisomant are also higher, being more than 90% in clinical trials and 63% in a large databank of real‐life treatment . Therefore, the control rate we found with CAB is lower than that observed with other medical treatments in acromegaly …”
Section: Discussionmentioning
confidence: 60%
“…[28][29][30][31] Therefore, the control rate we found with CAB is lower than that observed with other medical treatments in acromegaly. 26,27,30,32 It is important to highlight that the control rate observed in our study probably overestimates the efficacy of CAB in monotherapy, as in our centre, only patients with less severe disease tend to be selected for CAB treatment in monotherapy. This potential bias was mainly due to the previous data in the literature showing that those patients with mild disease are the ones with a better chance of disease control with CAB.…”
Section: Discussionmentioning
confidence: 70%